The Spread of Ottoman Khaṭṭ in Indonesia with Reference to the Sanad of Belaid Hamidi and Its Impact - Ulya, Nurun Najmatul; Amrulloh, Ahmad Yasir; A’bdussamad, Nur Fathiah binte (Jurnal Lektur Keagamaan, 2025)
The art of Arabic calligraphy (khaṭṭ), regarded as both an aesthetic and scholarly discipline, is grounded in a tradition of scientific lineage (sanad), particularly since the Ottoman (ʿUthmānī) period. However, scholarly exploration of this lineage in the Indonesian context has been notably lacking. This study aims to investigate the dissemination of khaṭṭ sanad from the Ottoman period in Indonesia, with a specific focus on the lineage of the Moroccan calligrapher Belaid Hamidi. Employing library research methods, supported by field observations and interviews with Indonesian calligraphers trained under Hamidi, the study identifies three key findings. First, the foundational transmitters of khaṭṭ sanad during the Ottoman period are as follows: Ḥamdullāh al-Amāsī for Naskh and Thuluth scripts; Ismāʿīl Ḥaqqī Ṣāmī Afandī for Dīwānī and Dīwānī Jaly; Muḥammad Asʿad al-Yāsarī for Taʿlīq; and Mumtāz Bīk for Riqʿah. Second, Belaid Hamidi, who received training from Turkish masters, became the conduit for transmitting these calligraphic lineages to Indonesia. Third, the sanad was disseminated in Indonesia through five of Hamidi's students who studied with him in Egypt: Muhammad Nur (Ponorogo), Nur Hamidiyah (Ngawi), Alim Gema Alamsyah (Tangerang), Khoiru Rofiqi (Aceh), and Shahryanshah Sirojuddin (Kalimantan). These individuals have since extended the reach of the sanad through pesantren and university-based initiatives, contributing to the revitalization and localization of Ottoman calligraphic traditions in Indonesia.